Hal Hal Mengasihi Sesama dan Musuh: Refleksi Dari Lukas 6:27-36 terhadap Konteks Dialog Beragama: Loving One’s Neighbor and Enemies: A Reflection on Luke 6:27–36 in the Context of Interreligious Dialogue - Andri Togatorop; Natanael Winanto; Suriawan Suriawan (Sekolah Tinggi Teologi Widya Agape dan Perkumpulan Teolog Agama Kristen Indonesia, 2024)
This article discusses the concept of love within the context of Christian teachings, specifically in the relationships among people living in pluralistic societies.